Analysis and Design of Decision Support System Systems in Choosing the Best Supplier Using the TOPSIS Method at PT. Bintang Putra Mandiri - Kelvin Tri Tama; Andi Leo (Tech-E, 2019)
Analysis and design of a decision support system aims to deal with problems in selecting the best supplier which is a problem at PT. Independent male star. PT. Bintang Putra Mandiri is a company engaged in the subsidized housing contractor and developer. With the existing problems, we need a system that can help companies to help determine the best supplier. Then produced a system that can help companies by using the TOPSIS method. TOPSIS uses the principle that the chosen alternative must have the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution from a geometric point of view using the Euclidean distance to determine the relative proximity of an alternative to the optimal solution. As a result, PT. Bintang Putra Mandiri can determine the best supplier precisely. And the TOPSIS method is able to support supplier selection decisions by ranking